Establishing a Successful Basic Science Research Program in Colon and Rectal Surgery - Leeds, Ira; Wick, Elizabeth C. (Clinics in Colon and Rectal Surgery, 2014)
Although at first glance, the surgeon-scientist appears to be a rare breed in today's clinical revenue-driven world, with careful planning and mentorship this is still a vibrant career path. If one is considering this avenue, it is important to seize even small opportunities to pursue laboratory work during training—summers in college and medical school, rotation blocks, and dedicated time in the middle of residency. Publications and small grants during these times will lay the ground work for future success. When considering a faculty position, it is essential to identify a mentorship environment that has a track record for success—either in the department of surgery or anywhere in the university. Ensuring adequate support from the department of surgery chair and division leader is essential. Basic science careers take years for the return in investment to be manifested! Also critical is to secure extramural funding early in the faculty stint—first foundation grants and then National Institutes of Health–mentored scientist funding. Surgeons provide a unique perspective in basic science work and it is critical that we continue to support young surgeons in this career path.
Keywords: surgeon; K08; basic science; mentorship; NIH